PENINGKATAN KINERJA UMKM MELALUI PENGELOLAAN KEUANGAN (JEA17: Jurnal Ekonomi Akuntansi, 2022)
From the research entitled "The Influence of Financial Management in Improving the Performance of Micro, Small and Medium Enterprises (UMKM) in Surabaya" this study aims to analyze good financial management in improving the performance of UMKM. This research was conducted in Surabaya, East Java. The object of this research, namely the influence of financial planning, financial records, and the separation of personal financial statements and business finances on the performance of UMKM. This study uses a sample of UMKM in Surabaya. In this study, the sampling technique used a non-probability sample, because the researcher did not get the details of the respondent's identity needed in making the sampling frame. Non-probability method using purposive sampling technique. Purposive sampling is a sampling technique based on special criteria, namely business actors in Surabaya. The analysis used is multiple linear regression. The results of this study are that the value of the financial planning variable has a value of 0.21, and financial records have a value of 0.19, and the separation of personal financial statements and business finances has a value of 0.15 which means that each of these variables has a significant effect on the performance of UMKM..